Current State of Youth Employment in the Republic of Sakha (Yakutia) - Pavlovna Pavlova, Ekaterina (2020)
The relevance of this research is evident as the problems of the modern market economy and the financial system of the global world economy are highly pertinent to economic science. In the modern world, on its way to globalization, the ability to promptly adapt to the conditions of international competition is becoming instrumental for ensuring successful and sustainable development. The primary competitive advantage held by a highly developed country is related to the possibility of updating its human development index, which is largely determined by the state of its education system. Thus, this area is connected to the country’s sustainable economic growth over the medium and long terms; the employment of fresh graduates is a complex, relevant and multifaceted problem, since it affects almost all segments of society. Currently, in view of the rapidly evolving situation in the labor market, the threat of unemployment for recent graduates is becoming extremely acute. Today’s graduates replenish vulnerable social groups that are suffering from difficult life situations. The purpose of this study is to analyze the state of employment of university graduates, as exemplified by the employment of recent graduates, and to provide recommendations to assist in their recruitment. A combination of theoretical (analysis, generalization while establishing principles and patterns), organizational (comparison, longitudinal method) and empirical (sociological methods, observational methods, quantitative method of statistical processing of the collected data and interpretation method) methods was used in the research. As part of the study, knowledge regarding the primary factors affecting high school graduates’ employment is defined and systematized. The practical and theoretical significance of the study lies in the recommendations developed for promoting university graduates’ employment in the Republic of Sakha (Yakutia) [RS (Y)] based on the results obtained.